Adaptation of Digital Perception Service and Communication Technologies for Local Communication Network of Urban Grid - Cheng ZHONG; Di ZHAI; Yang LU; Jingyi FAN; Xiaobo LIU; Xinyue ZHANG; Xiongwen ZHAO (Zhongguo dianli)
In view of the requirements of the differentiated new local digital power perception service for communication performance, the adaptation of flexible and reasonable communication technology is essential to establish a safe, reliable and economic power communication network. Aiming at the new local digital perception scenarios of the new power system, an analysis is firstly carried out on the requirements for the communication performance of the typical local communication technology and power business, and a multi-level and multi-dimensional comprehensive evaluation model is constructed. Secondly, a combined subjective and objective weighting method by fuzzy analytic hierarchy process-entropy weight based on correlation coefficient is proposed to determine the weights of indexes. And finally, the best fit-technique for order preference by similarity to ideal solution (BF-TOPSIS) is used to calculate the weighted evaluation scores to obtain adaptation results. The results show that the proposed evaluation model and adaptive algorithms can provide a theoretical basis and solutions for matching between new local digital power perception services and local communication technologies.